Manajemen Pengelolaan Sumber Daya Pendidikan di Madrasah Ibtida'iah Muhammadiyah Innovative Gonilan Kartasura - Triyanto, Joko; , Dr. Sabar Narimo,M.M.,M.Pd; , Dr. M. Muhtarom,S.H.,M.H (2016)
This study analyzed how the management model which includes the Education Resource Teacher Competence, Teaching and Learning, Extracurricular Activities and Infrastructure in Madrasah Ibtida'iah Muhammadiyah Innovative Gonilan Kartasura, Sukoharjo. Objective: (1) Analyzing the Master in Madrasah Ibtida'iah Muhammadiyah Innovative Gonilan Kartasura, Sukoharjo, (2) analyze the learning process in Madrasah Ibtida'iah Muhammadiyah Innovative Gonilan Kartasura, Sukoharjo, (3) Analysis of Infrastructure in Madrasah Ibtida'iah Muhammadiyah Innovative Gonilan Kartasura, Sukoharjo, (4) Analyzing the Extracurricular Activities in Madrasah Ibtida'iah Muhammadiyah Innovative Gonilan Kartasura, Sukoharjo. This study used descriptive qualitative method. Collecting data using observation, interview techniques and engineering documents. Form of analysis is the interpretation of the data. Test the validity of the data using triangulation techniques or data source. The findings of the study are: analysis of the management of educational resources in Madrasah Ibtida'iah Muhammadiyah Innovative Gonilan Kartasura, Sukoharjo ; (1) Competence good Master, (2) methods of teaching and learning process, (3) adequate facilities and infrastructure (4) Extracurricular Activities.